Chapter 1 The non-patient's view - Worboys, Michael (Social Histories of Medicine, 2021)
Since Roy Porter's pioneering work on the 'patient's view', historians have taken up the challenge to rewrite medicine's past 'from below'. However, this chapter argues that they have not been radical enough and have neglected a key part of Porter's agenda for the new social history of medicine. He wrote: 'We should stop seeing the doctor as the agent of primary care. People took care before they took physick. What we habitually call primary care is in fact secondary care, once the sufferer has become a patient, [and] has entered the medical arena.' In other words, the beliefs, behaviour and actions of sick people who did not go to the doctor and remained 'non-patients'. To explore the 'non-patient's view', we have to look beyond self-care and the use of proprietary remedies and alternative medicine. The sociological term of the 'symptom iceberg', which refers to the aches and ailments that never reach the doctor, is used as a guide. In turn, historical examples to the following responses to symptoms are discussed: doing nothing; prayer; finding information; looking to family and friends; over-the-counter medicines. The chapter suggests how historians can research the 'non-patient's view', by interrogating familiar sources in new ways and finding novel sources, many of which will have previously been regarded as non-medical. Finally, the chapter considers the policy implications of this work in terms of recent attempts to ease pressures on healthcare systems that encourage people 'not to see the doctor' and opt for self-care.